FORECASTING ANALYSIS OF CHICKEN MEAT PRODUCTION AND CONSUMPTION (BROILER) IN NORTH SUMATRA PROVINCE - Febry Hardian (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
This study aims to analyze the production and consumption of broiler meat in North Sumatra Province with forecasting analysis using the SPSS program application. The method of determining the area used is purposive area sampling. The data used in this study are secondary data obtained from the Central Statistics Agency and the Department of Animal Husbandry and Food Security, North Sumatra Province. The results showed that in 2006-2015 in North Sumatra Province, broiler chicken meat production experienced a positive trend and for broiler chicken meat consumption also experienced a positive trend. In 2006-2015 in North Sumatra Province, broiler meat consumption was greater than broiler meat production in North Sumatra Province. For the years 2016-2025 in North Sumatra Province, it shows that the results of forecasting analysis of broiler meat production have a negative trend and the results of forecasting analysis of broiler meat consumption experience a negative trend which decreases with not too significant differences between the results of forecasting analysis of chicken meat production and consumption. broilers in North Sumatra Province.